Nomadic Performativity and the Immanent Ethics of Life - Žukauskaitė, Audronė (Nordic Theatre Studies, 2015)
This essay discusses Gilles Deleuze and Félix Guattari’s notion of nomadology, which can be used as the basis for an ontological and aesthetic alternative to our understanding of representational theatre. Referring to different meanings of nomadology, the essay argues for the notion of nomadic performativity, which can be applied to recent non-representational performative practices. For this purpose the essay makes an indirect comparison between Deleuze and Guattari’s philosophical ideas and their sporadic insights into art, such as Francis Bacon’s paintings and Antonin Artaud’s theatre. Deleuze discusses theatre in “One Less Manifesto”, his only text directly dedicated to theatre and to Carmelo Bene’s productions. Referring to the structural deformations in Bene’s work, Deleuze argues for non-representational theatre, based not on representation and identity but on continuous variation and differentiation. In other words, if theatre as a form of representation creates a striated and hierarchized space that embodies and increases power, the non-representational theatre creates a nomadic smooth space of continuous variation, which transposes everything into a constant becoming. In this respect nomadic performativity covers these meanings: first, it is a distribution of intensities, which come to replace forms, bonds, organized hierarchies; second, it refers to fusional multiplicities rather than self-identical subjects; and third, it opens up the potential for change and “becoming-minor” instead of representing major figures of power.